Report of the Indian Famine Commission 1901 - Planning Commission (Planning Commission, 1901)
The 1901 Indian Famine Commission Report analyzes the 1899-1900 famine, evaluating historical failures, relief administration, and agricultural conditions in British India. It highlights high mortality rates due to disease and inadequate relief, emphasizing the importance of timely intervention, daily wage payments, and robust medical support. Recommendations include improved famine preparedness, systematic relief distribution, monitoring of distress signals, and local government engagement. The report also addresses agricultural development through irrigation, cooperative credit systems, and reforms in land revenue policies to prevent indebtedness. Overall, it advocates an integrated approach combining economic, agricultural, and public health measures to mitigate famine impacts, promote rural stability, and ensure long-term food security.
Calcutta: Office of The Superintendent of Government Printing, India, 1901.
Calcutta: Office of The Superintendent of Government Printing, India, 1901.
Keywords: Indian Famine Commission; Famine Relief; Wage Policies; Agricultural Loans; Irrigation Development; Mortality Rates; Land Revenue; Agricultural Productivity; Rural Indebtedness; Public Health